NDUSTRY 4.0 DETERMINANTS AND COMPETITIVE ADVANTAGE- A STUDY ON MALAYSIAN SMEs - Mohammad Nurul Hassan Reza , Sreenivasan Jayashree (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study explores the major influencing determinants shaping Industry 4.0 and its impact on competitive advantage in the aspect of Malaysia. SMEs are one of the essential players in the economy, attaining high expectations from customers and stakeholders. The Fourth Industrial Revolution can be denoted as Industry 4.0, which can meet the expectations as it has emerged with modernization and tremendous technological improvement. This revolution can transform products and production systems through real-time data synchronization, thus can satisfy the customers with modified products. The novelty of Industry 4.0 and its intrinsic complexity in recognizing the determinants need to be explored as most recent studies discuss the technological aspect. The findings would help to have useful insights for SMEs looking to step up modernization initiatives with Industry 4.0. This study proposes a conceptual model with several hypotheses that will be tested through a quantitative analysis for further research among Malaysian SMEs. Structural Equation Modeling (SEM) will be used for data analysis.